Trained by Demonstration Humanoid Robot Controlled via a BCI system for Telepresence - Saduanov, Batyrkhan; Alizadeh, Tohid; Abibullaev, Berdakh; An, Jinung (Nazarbayev University School of Science and Technology, 2018)
Onerous life of paralyzed people is a substantial problem of the world society and improving their life quality would be a great achievement. This paper proposes a solution in this regard based on telepresence, where a patient perceives and interacts with a world through an embodiment of a robot controlled by a Brain-Computer Interface (BCI) system. The proposed approach brings together two leading techniques: Programming by Demonstration and BCI. Several tasks could be learned by the robot observing someone performing the function. The end user would issue commands to the robot, using a BCI system, concerning its movement and the tasks to be performed. An experiment is designed and conducted, verifying the applicability of the proposed approach.
2018 6th International Conference on Brain-Computer Interface (BCI)
Keywords: Brain-Computer Interfaces; Brain computer interface; Computer Systems; Demonstrations; Robots; Quality of Life; Experiments